BIOEQUIVALENCE STUDY OF ANTIDIABETIC ACTIVITY BETWEEN TWO MARKETED FORMULATIONS OF METFORMIN ON GLUCOCORTICOID-INDUCED HYPERGLYCEMIA IN RABBIT - Das, Debanga; Chakraborty, Jashabir; Dash, Suvakanta (International Journal of Current Pharmaceutical Research, 2017)
Objective: Bioequivalence studies are the commonly accepted methods displaying therapeutic equivalence between two products. This study was conducted to evaluate the bioequivalence study of anti-diabetic activity between two formulations of metformin tablets which were marketed in India. Methods: In in vitro study five essential in vitro tests including disintegration, weight variation, hardness, friability and a comparative in vitro dissolution study were performed. Results: For in vivo study adult male rabbits were divided into three groups of two each. The first group is regarded as control group received 3 ml of normal saline daily by using the gastric tube for 15 d and the second and third group received (0.35 mg/Kg B.W. single dosage) of dexamethasone tablets which were powdered, dissolved in 3 ml of normal saline daily for 15 d. After 15 d the blood glucose of second and third group was estimated and after that received formulation X and formulation Y, dissolved in 3 ml of normal saline daily for 15 d at the dose of 0.5 gm/kg body weight orally. After 15 d again blood glucose of second and third group was estimated and compare the results of both the group. This shows the favourable response of metformin against glucocorticoid-induced renal damage and hyperglycemia. Conclusion: Results of this study showed that the extent, rate of absorption and anti-diabetic activity of two different formulations of metformin tablets are bioequivalent to each other.